Practice-Based Learning and Improvement: Improving Residents' Performance in Providing Preventive Care Through a Web-Based Chart Audit System - Carolyn Stalvey; Richard Rathe (Association of American Medical Colleges, 2008)
Abstract This resource is a web-based self-assessment tool and audit system for internal medicine residents to evaluate their health-screening practices in their continuity clinics. This program allows residents to evaluate their knowledge of and compliance with the U.S. Preventive Services Task Force and the American Diabetes Association disease prevention screening guidelines in their own clinics. In this resource, residents complete pre- and postquizzes to assess their medical knowledge of current screening guidelines. Residents review the medical records of 10 patients who were recently seen in their continuity clinic. For each patient, the program asks a series of questions for each screening test or immunization. For example: "Is pneumococcal vaccine polyvalent recommended for this patient?" The residents then indicate why the vaccine is or is not recommended for the patient by choosing from a list of indications for the pneumococcal vaccine polyvalent. The program covers 16 preventative health-screening tests, including colon cancer screening, mammography, influenza vaccine, and hemoglobin A1C testing. The program generates a performance report for each resident, and the resident then completes a self-reflection form. The residency associate program director reviews the performance report and sends a letter to the resident and the resident's continuity clinic preceptor summarizing performance, areas of strength, and areas to improve. Residents have given overwhelmingly positive feedback on this program and have stated they are using it to improve their own practice habits. Continuity clinic attendings have noted an increase in residents' emphasis on preventative health screenings in the ambulatory setting.